Tatuagem na prisão: estigma & identidade. - Chaves, Karine Belmont (2013)
This dissertation aims to seek the understanding of tattooing in prison and the unfolding of the tattoo as a form of expression, individual and group belonging and identification, stigmatizing and marginalizante in this context. Under an interdisciplinary perspective, the survey was conducted at the State Penitentiary in Foz do Iguaçu, Paraná State, by obtaining data on primary sources as the identification records of prisoners and meanings of tattoos, bibliographic sources, participant observation and interviews semi-dirigidas. In this criminal unit, 64% of the prisoners who meet in closed regime have tattoo and we see that the people arrested "choose" their tattoos and their symbols conditioned by criminal involvement. In this way, the use of tattooing in this context indicates belonging to the group, identifying with the criminal activity, marginalization by the stigma, but also strengthening of the affective links with family members. Tattooed symbols differ from used out of prison, as it differs the quality of tattoo held in prison, without the materials, techniques and skills desirable. Although the tattoo is today a "cultural phenomenon", in many cases it even configures stigma, because it represents an identification code of "criminal", mainly for public safety professionals.